Effects of the physiological age of seed potatoes on tuber initiation and starch and dry matter accumulation - Caldiz, Daniel O.; Brocchi, Gabriel; Alaniz, Jorge; Marchan, Carmen (Pesquisa Agropecuaria Brasileira, 1996)
The physiological age of seed potato tubers (Solanum tuberosum L.) modifies several morphological, physiological and agronomic characteristics of the crop. However, there is little evidence on the possible influence of physiological age upon the mechanism involved in tuber initiation and starch accumulation. This study investigated the effects of the physiological age of seed tubers on tuber initiation, starch synthase activity and dry matter accumulation and distribution. Physiologically aged seed potatoes promoted an early tuber initiation in the following crop. Early in the sewn the stolon tips of these plants showed an increase in starch synthase activity and an anticipated starch accumulation. During the rest of the season the starch synthase activity in the stolon tips of tubers grown from young seed was higher than those grown from the physiologically older ones, which decreased by day 70 after planting. Dry matter accumulation by leaves and stems did not differ between treatments, while tuber dry matter accumulation was higher in those plants originated from physiologically young tubers. These results confirmed that physiologically old seed anticipates tuber initiation and demonstrated that the pattern of starch synthase activity, starch accumulation and dry matter accumulation and distribution depends on the physiological age of seed tubers.